2016
DOI: 10.1113/ep085665
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin mass alterations in healthy humans following four‐day head‐down tilt bed rest

Abstract: Rapid decreases in hemoglobin mass (Hbmass) have been reported in healthy humans following spaceflight and descent from high altitude. It has been proposed that a selective increase in the destruction of young red blood cells (RBCs) mediates these decreases but conclusive evidence demonstrating neocytolysis in humans is lacking. Based on the proposed triggers and time course of adaptation during spaceflight, we hypothesized that Hbmass would be reduced following 4 days of −6° head-down tilt bed rest (HDTBR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
0
8
2
Order By: Relevance
“…Hemolysis phenomenon is biologically characterized by increased serum unconjugated bilirubin levels, combined in case of intravascular hemolysis, to a reduction of serum haptoglobin level 42 . Previous studies evaluating these markers observed that serum bilirubin levels remained unaffected in humans exposed to real or simulated microgravity, thus suggesting that significant hemolysis did occur under microgravity 36,43,44 . In contrast, we observed that 5 days of DI increased both serum unconjugated bilirubin and haptoglobin levels, suggesting that if hemolysis occurs under DI, this hemolysis is extravascular 45 .…”
Section: Discussioncontrasting
confidence: 47%
“…Hemolysis phenomenon is biologically characterized by increased serum unconjugated bilirubin levels, combined in case of intravascular hemolysis, to a reduction of serum haptoglobin level 42 . Previous studies evaluating these markers observed that serum bilirubin levels remained unaffected in humans exposed to real or simulated microgravity, thus suggesting that significant hemolysis did occur under microgravity 36,43,44 . In contrast, we observed that 5 days of DI increased both serum unconjugated bilirubin and haptoglobin levels, suggesting that if hemolysis occurs under DI, this hemolysis is extravascular 45 .…”
Section: Discussioncontrasting
confidence: 47%
“…The current study benefitted from direct measures of hemolysis in healthy men in laboratory conditions. Ryan et al (2016) completed a 4-day HDT bed rest study on seven subjects and reported a similar sequence of changes for most measures including decreased plasma volume, hemoconcentration during bed rest, and decreased tHb after bed rest. Interestingly, they also reported decreased hemolysis at 4 days of bed rest.…”
Section: Reambulation After Bed Restmentioning
confidence: 91%
“…This may be of high clinical significance since erythrocyte loss from prolonged bed rest partly explains the unpredictable anemia in bed-ridden patients or in people with decreased mobility ( Guralnik et al, 2004 ), an extremely prevalent defect in the elderly population. An often-ignored finding that warrants further investigation is that erythrocytes recover four weeks after the bed rest-induced, decreased production rather than increased haemolysis ( Ryan et al, 2016 ).…”
Section: Space Anemiamentioning
confidence: 99%